Comparative Genomics and Evolution of Avian Specialized Traits - Wu, Lei; Jiao, Xiaolu; Zhang, Dezhi; Cheng, Yalin; Song, Gang; Qu, Yanhua; Lei, Fumin (Current Genomics, 2021)
Genomic data are important for understanding the origin and evolution of traits. Under the context of rapidly developing of sequencing technologies and more widely available genome sequences, researchers are able to study evolutionary mechanisms of traits via comparative genomic methods. Compared with other vertebrates, bird genomes are relatively small and exhibit conserved synteny with few repetitive elements, which makes them suitable for evolutionary studies. Increasing genomic progress has been reported on the evolution of powered flight, body size variation, beak morphology, plumage colouration, high-elevation colonization, migration, and vocalization. By summarizing previous studies, we demonstrate the genetic bases of trait evolution, highlighting the roles of small-scale sequence variation, genomic structural variation, and changes in gene interaction networks. We suggest that future studies should focus on improving the quality of reference genomes, exploring the evolution of regulatory elements and networks, and combining genomic data with morphological, ecological, behavioural, and developmental biology data.
Keywords: evolution